Deglacial floods in the Beaufort Sea preceded Younger Dryas cooling - Keigwin, L. D.; Klotsko, S.; Zhao, N.; Reilly, B.; Giosan, L.; Driscoll, N. W. (Nature Geoscience, 2018)
A period of cooling about 13,000 years ago interrupted about 2,000 years of deglacial warming. Known as the Younger Dryas (YD), the event is thought to have resulted from a slowdown of the Atlantic meridional overturning circulation in response to a sudden flood of Laurentide Ice Sheet meltwater that reached the Nordic Seas. Oxygen isotope evidence for a local source of meltwater to the open western North Atlantic from the Gulf of St Lawrence has been lacking. Here we report that the eastern Beaufort Sea contains the long-sought signal of O-18-depleted water. Beginning at similar to 12.94 ± 0.15 thousand years ago, oxygen isotopes in the planktonic foraminifera from two sediment cores as well as sediment and seismic data indicate a flood of meltwater, ice and sediment to the Arctic via the Mackenzie River that lasted about 700 years. The minimum in the oxygen isotope ratios lasted similar to 130 years. We suggest that the floodwater travelled north along the Canadian Archipelago and then through the Fram Strait to the Nordic Seas, where freshening and freezing near sites of deep-water formation would have suppressed convection and caused the YD cooling by reducing the meridional overturning.

The deglacial history of surface and intermediate water of the Bering Sea - Cook, M. S.; Keigwin, L. D.; Sancetta, C. A. (Deep-Sea Research Part Ii-Topical Studies in Oceanography, 2005)
The lithology of deglacial sediments from the Bering Sea includes intervals of laminated or dysaerobic sediments. These intervals are contemporaneous with the occurrence of laminated sediments from the California margin and Gulf of California, which suggests widespread low-oxygen conditions at intermediate depths in the North Pacific Ocean. The cause could be reduced intermediate water ventilation, increased organic carbon flux, or a combination of the two. We infer abrupt decreases of planktonic foraminifer delta(18)O at 14,400 and 11,650 yr BP, which may be a combination of both freshening and warming. On the Shirshov Ridge, the abundance of sea-ice diatoms of the genus Nitzschia reach local maxima twice during the deglaciation, the latter of which may be an expression of the Younger Dryas. These findings expand the extent of the expression of deglacial millennial-scale climate events to include the northernmost Pacific. (c) 2005 Elsevier Ltd. All rights reserved.
995ksTimes Cited:51Cited References Count:52

Detecting holocene changes in thermohaline circulation - Keigwin, L. D.; Boyle, E. A. (Proc Natl Acad Sci U S A, 2000)
Throughout the last glacial cycle, reorganizations of deep ocean water masses were coincident with rapid millennial-scale changes in climate. Climate changes have been less severe during the present interglacial, but evidence for concurrent deep ocean circulation change is ambiguous.
Keigwin, L DBoyle, E A eng Research Support, U.S. Gov't, Non-P.H.S. 2000/03/04 09:00 Proc Natl Acad Sci U S A. 2000 Feb 15;97(4):1343-6.
Keywords: *Climate; *Plankton; Animals; Atlantic Ocean; carbon isotopes; ice; oxygen isotopes; time

Deep-sea sediments reveal - Lehman, Scott J.; Keigwin, L. D. (Oceanus, 1993)
id: 1248